3D Coseismic Surface Displacements From Historical Aerial Photographs of the 1987 Edgecumbe Earthquake, New Zealand. Issue 11 (10th November 2022) - Delano, J. E.; Howell, A.; Stahl, T. A.; Clark, K.
Abstract: Earthquake surface deformation provides key constraints on the geometry, kinematics, and displacements of fault rupture. However, deriving these characteristics from past earthquakes is complicated by insufficient knowledge of the pre‐event landscape and its post‐event modification. The 1987 M w 6.5 Edgecumbe earthquake in the northern Taupō volcanic zone (TVZ) in New Zealand represents a moderate‐magnitude earthquake with distributed surface rupture that occurred before widespread high‐resolution topographic data were available. We use historical aerial photos to build pre‐ and post‐earthquake digital surface models (DSMs) using structure‐from‐motion techniques. We measured discrete and distributed deformation from differenced DSMs and compared the effectiveness of the technique to traditional field‐ and lidar‐based studies. We identified most fault traces recognized by 1987 field mapping, mapped newly identified traces, and made dense remote slip measurements with a vertical separation resolution of ∼0.3 m. Our maximum and average vertical separation measurements on the Edgecumbe fault trace (2.5 ± 0.3 and 1.2 m, respectively), are similar to field‐based values of 2.4 and 1.1 m, respectively. Importantly, this technique can discern between new and pre‐existing fault scarps better than field techniques or post‐earthquake lidar‐based measurements alone. Our surface displacement results are used to refine subsurface fault geometries and slip distributions at depth, which are further used to investigate potential magmatic‐tectonic stress interactions in the northern TVZ. Our results suggest the Edgecumbe fault dips more gently at depth than at the surface, hosted shallow slip in 1987, and may be advanced toward failure by interactions with nearby magma bodies. Plain Language Summary: Understanding earthquake behavior relies heavily on information about how past earthquakes changed the landscape. Detailed information about the surface topography before the earthquake is often limited, creating challenges for accurately measuring earthquake surface deformation. Aerial photos are widely available and can be used to create 3D digital surface models in places where other topographic information is lacking. We use historical aerial photos to make 3D datasets of the surface topography before and after the 1987 Edgecumbe earthquake in New Zealand. We calculated the difference between the two 3D datasets to identify and measure how the earthquake changed the landscape, and compared our results to previous measurements. We found that this method generally works as well as field methods for identifying and measuring fault movement, and has some advantages over other techniques. In particular, this approach can separate deformation from individual earthquakes, which had previously been a challenge. The results refine our understanding of the faults below the surface, provide insight into the earthquake's relationship to surrounding faults and volcanic systems, and allow us to better characterize seismic hazard both here and in other similar geologic settings. Key Points: Historical aerial photos can be used to generate pre‐ and post‐earthquake digital surface models for measuring displacement This method performs at least as well as field surveys, and better captures single‐event displacements to constrain earthquake behavior The Edgecumbe earthquake is important for understanding low dip‐angle normal fault ruptures and possibly magma‐tectonic interactions